The effectiveness of narcotics rehabilitation program in Malaysia - Ibrahim, Fauziah; Abu Samah, Bahaman; Subhi, Nasrudin; Jusoff, Kamaruzaman; Mohamad, Mohd Suhaimi; Sarnon @ Kusenin, Norulhuda; Chong, Sheau Tsuey; Mohamad, Lukman @ Zawawi (IDOSI Publications, 2011)
The goal of treatment is to return the individual to productive functioning in the family, workplace and community. This article is provided to examine the level of effectiveness of narcotic addiction recovery program on drug addicting relapse and to determine the relationship between effectiveness of narcotic addiction recovery program towards addicting relapse in Malaysia. Data were collected through a self-administered questionnaire. Data collected were analyzed using 'SPSS for Windows'. The sample consisted of 400 relapsed drug addicts being selected through stratified random sampling and systematic random sampling from eight Narcotic Addiction Recovery Centers throughout Peninsular Malaysia. This research is a quantitative method and cross sectional survey. The quantitative data were analyzed using analysis Pearson correlation and descriptive tests. The findings indicated that about 98.5% of respondents experienced a moderate to high level toward the program. Pearson correlation analyses indicated that there is no relationship between overall drug rehabilitation program (r=-.049, p>.05) included program phase one (r=-.010, p>.05), phase two (r=-.074, p>.05), phase three (r=-.017, p>.05) and phase four (r=-.042, p>.05) toward relapsed addictions. The conclusion reflects that the drug rehabilitation program by the government to rehabilitate addicts is not the main factors that contributing to the relapsed addiction tendency in Malaysia.